TANGGUNG JAWAB TERHADAP PROTOKOL NOTARIS SEBAGAI AKIBAT DITETAPKANNYA NOTARIS MENJADI PEJABAT NEGARA - Adi Putra, Fauzan (UNES Law Review, 2023)
Responsibility for the Notary Protocol is regulated in the Notary Office Law Number 30 of 2004 as amended to become Law Number 2 of 2014 concerning the Position of Notary (UUJN). Notary Protocol is a collection of documents constituting State Archives that a Notary must keep and maintain. This normative legal research method is an attempt to see how the application of positive law to the Notary Protocol's accountability process from Notaries who will be appointed as State Officials. Research Results 1) Arrangements that have been arranged have not been implemented, the Notary is not responsible for appointing a Substitute Notary and is negligent of the Protocol. 2) The Regional Supervisory Council has not implemented the rules and procedures that have been regulated in UUJN and the Regulations of the Minister of Law and Human Rights. 3) The legal consequences that are regulated are not carried out. A Notary appointed as a State Official must take leave because a Notary is prohibited from holding multiple positions.